Natura unitatis ecclesiae et eventa anno domini 1054 - Bendza, Marian (Vox Patrum, 2016)
This article above could be called as a supplement to the History of the Church – it has been written not to present in a narrative way the common-known course of the East-West Schism which began in the 11th century, but to give some remarks and to present some little known details, which could be helped to create a new dimension of reflexion, and even of discussion on problems included in this article. The event of the 1054th in modern historiography are treated as absolutely end of the “Church unity indivisibility period”. This point of view does not divide the Author of this article, so he decided to present a new- quality-reflexion, thanks of it the described events could be recognized as the consequence of earlier revealing trends. The Author also shows, that the Church unity is not so clear, because in the Church History you can meet some separatist tendencies. It is but very important, that no one of them could foil the principal ecclesiastical hallmark, the Unity. This Unity could situate the reality of Church in the God’s Plan of Salvation, making it independent from human decisions, disagreement cases or arrogance. The unity reflexion based both on the biblical and patristic analysis, permit us in new way treat the events of 1054th. Their “schismatic” character, especially in context of the patristic texts seems to by rather a heated discussion, in which both interested parts desire in cooperation to respond their epoch challenge. It was, after all, the great epoch of the Gregorian Roman Catholicism reform and of “theological Byzantine golden age”. So it should be better, when we treat the Schism simple as a division, and in the rough Hierarchy’s declarations we find signs of Church responsibility. This way of thinking is justified by creating Normans’ power and increasing problems with Caesaropapism tendencies. The conclusion of this article is clear: in consequence of the 1054th events “Byzantine Golden age” was about to be broken, but the Church Unity remained untouched…